Quality of life in freshmen college students of physical education courses Qualidade de vida em acadêmicos ingressantes em cursos de educação física - Claumann G.S.* (2017)
© J. Phys. Educ., 2016.This study aimed to analyze the quality of life in freshmen college students of Physical Education courses and compare it between sex, courses, weight status, body image and physical activity level of the participants. Participants were 198 college students (Bachelor= 104 and Licentiate= 94), with a mean age of 20.6 (4.6) years. Participants answered a questionnaire about their sex, age, body mass and height (for BMI calculation and weight status classification), body image (figure rating scale), physical activity level (IPAQ short form) and quality of life (WHOQOL-Bref). Mean score of quality of life was 74.9 points. Better quality of life was founded in physical and social domains and worst quality of life in environmental domain. Differences were observed in general quality of life, and physical, psychological and social domains between body image categories. There was also difference in general quality of life and physical and environmental domains between physical activity levels. Concluding, college students had good quality of life. Compared to peers, the ones dissatisfied with their body image had lower quality of life and the physically actives, higher. There was no difference in quality of life between sex, courses or weight status.